AN OPEN LETTER FROM AN AFRICAN WOMEN SCIENTIST TO RESEARCH ETHICS COMMITTEES - Deguenon, Esther (Filanderas, 2021)
With inspiring backgrounds, challenges, rich and diverse experiences, African women in science have proven that gender does not matter as long as you have the will and passion. But how many of these women today are recognised for their daily work? From the difficulty of evolving in a male-dominated environment to the challenges of entering a new field, many are the challenges African women face in finding their place in science. African women scientists face the hardship of being a female scientist every day and of being considered the weaker sex. It would be very useful to strengthen the networks of women scientists by facilitating access to information for women scientists and to get them to support each other and, specially, to the younger ones who want to pursue a career in science. African women scientists deserve to be protected in their scientific activities by applicable and binding texts. This is a letter read by its author to members of the Aragón Research Ethics Committee and of the National Ethics Committees of Benin, Guinea Bissau, Guinea Conakry, Mali and Senegal during the opening of the University of Zaragoza-led 2nd International Congress on the Harmonisation of Gender Mainstreaming in West Africa.
Keywords: Female scientist; Challenges; Gender equality; Female solidarity; Ethics